Prevalence of Fascioliasis and Associated Economic Losses in Cattle Slaughtered at Lira Municipality Abattoir in Northern Uganda - Opio, Lawrence George; Abdelfattah, Essam M.; Terry, Joshua; Odongo, Steven; Okello, Emmanuel (Animals, 2021)
Fascioliasis (liver fluke infestation) is one of the most important parasitic diseases affecting cattle, other ruminant animals and humans. Fascioliasis causes large, but usually neglected, economic losses to cattle farmers and traders. The objectives of this study were to assess the prevalence and associated risks for fascioliasis in slaughter cattle and estimate the financial losses due to liver condemnation at the Lira Municipal abattoir in Uganda. A total of 216 cattle were sampled during the study period. Animal breed and sex were determined by observing the phenotypic characteristics of the animals. Age was determined by assessing the eruption and wearing of permanent teeth. After slaughter, the liver was examined for presence of Fasciola spp. (liver flukes) by visual inspection, palpation, and incisions. The bile ducts and gall bladder were similarly examined for presence of mature Fasciola spp. The gross weight and amount of liver trimmed-off due to fluke infestation were determined. Of the 216 liver examined, 65.7% (n = 142) were infested with Fasciola spp. Cattle that were aged 4–5 years old at the time of slaughter had significantly greater odds (OR = 5.84; CI [2.79–12.22]) of being infested with Fasciola spp. compared to those that were younger than 3.5 years old. In contrast, cattle that had a body condition score of 3.5 or 4 had lower odds (OR= 0.42; CI [0.21–0.88] and OR = 0.22; CI [0.04–1.10]) of fascioliasis than those with a BCS of 3. Other tested variables including animal origin, breed, sex, and gross weight of the liver had no significant effect on the prevalence of fascioliasis. This study also revealed that the abattoir loses an estimated 38 million UGX annually due to condemnation of Fasciola-infested liver (one UGX= 0.00027 USD; July 2016). Our study showed that the prevalence of fascioliasis was high in Lira District, Uganda, which results in a large amount of liver being condemned and destroyed, leading to financial losses for affected farmers in the area. Therefore, there is a need to take the necessary preventive measures to control the disease and increase awareness among farmers and medical personnel in the area due to the zoonotic nature of fascioliasis.
Keywords: Cattle; Fascioliasis; Economic loss; Prevalence